EMPOWERING INDIGENOUS STUDENTS THROUGH DIGITAL SKILLS AND CROSS-CULTURAL LITERACY: A COMMUNITY SERVICE PROGRAM IN MALAYSIA - Gusman Nawanir; Abrar Abrar; Dian Saputra; Rahmat Setiawan; Febrian Lisman (Jurnal Pengabdian Kompetitif, 2026)
This community service program aimed to empower Orang Asli (indigenous) students in Pahang, Malaysia, by enhancing their digital literacy and cross-cultural competencies. The program addressed the digital divide faced by indigenous students in higher education. A one-day intensive bootcamp was conducted on February 13, 2026, involving 30 participants from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and University College of Yayasan Pahang (UCYP). The methods included hands-on training on basic productivity software (Google Workspace, Microsoft Office), digital safety education, and career platform introduction. Partner satisfaction surveys showed 100% "Strongly Agree" responses on material relevance, delivery, capacity building, and program sustainability. The program successfully increased participants' digital confidence and basic skills. Partners explicitly recommended continuation and advanced software training. This initiative contributes to SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities